Analysis of physico-chemical parameters of water quality in and around Saltpans of Prakasam (Dt.) A.P - Kumari, B Lalitha; Sudhakar, P; sri, M Hanuma; Sree, K.P.N.V. Satya (Journal of Ecobiotechnology, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> One of the greatest challenges of the 21st Century is to provide an adequate supply of safe drinking water for house hold consumption to everyone. But today water pollution is the biggest problem for Human beings which deteriorates the water quality. Bore well and open well water were selected for analysis in the present study located in and around salt pans of Oollapalam and Ooguru of Prakasam (Dt.)in A.P. The potability, salinity and Water Quality Index of available water sources in that area were estimated in the present study. The analysed Physico-chemical Parameters in collected water were, pH,conductivity(mmhos),turbidity,total solids,total dissolved and suspended solids,total hardness,Ca & Mg hardness,chlorides,alkalinity,nitrates,sulphates, phosphates,DO,BOD & COD,Bo,Na,K etc. All these were analysed in mg/l and at last Sodium Absorption Ratio (mmol/l) was also calculated. All these were calculated by below mentioned formulas. The findings clearly indicated that saline effluent has polluted water and the results obtained indicate us that the detrimental impact of saline effluent on water quality rendering it unsuitable for the propagation of life and is unfit for agricultural purposes.